First-year follow-up of newborns operated for esophageal atresia in a developing country: Just operating is not enough! - Santosh Dey; Vishesh Jain; Sachit Anand; Sandeep Agarwala; Anjan Dhua; M Srinivas; Veereshwar Bhatnagar (Wolters Kluwer Medknow Publications, 2020)
Purpose: To identify complications, their incidence and risk factors for their occurrence in patients of esophageal atresia (EA) in the 1st year after discharge following surgery. Materials and Methods: Cases of EA discharged after surgical intervention in the period of July 2011-July 2013 were considered a cohort. All data regarding demographics, investigations, surgical procedure, outcome, and follow-up were recorded. Results: Seventy-six such patients were discharged in the study period, six of whom were lost to follow-up, and hence, seventy patients were included in the study. Of these 70, 48 (69%) had esophageal continuity restored (46 EA + tracheoesophageal fistula [TEF]; 2 pure EA), while 22 (31%) had been diverted (3 pure EA; 8 EA + TEF following major leak; 11 long gap EA + TEF). Risk of developing any complication (except death) was 48/70 (68%; 95% confidence interval [CI] = 57.4-79.7). Twenty-six of 48 patients with esophageal continuity restored, demonstrated narrowing on contrast study (54%; 95% CI = 39.5-68.7) but only 18 of these 48 (37.5%) had dysphagia. Thirty-one of seventy had an episode of lower respiratory tract infection (LRTI) (44.2%; 95% CI = 32.3%-56.2%). Poor weight gain was observed in 27/70 (37%), and this was significantly common in diverted patients (63% vs. 25%; P = 0.009). Twenty-one of total 70 (30%) patients died within the 1st year following discharge. Conclusions: Sixty-eight percent of cases developed some complication, while 30% succumbed within the 1st year of life following discharge. The common complications were stricture, LRTI, and poor weight gain. All of these were common in diverted patients.